Performance Evaluation Improvement of Energy Consumption in Ad-Hoc Wireless Network - et al., Mohammed Ayad Saad (International Journal of Advanced Science and Technology, 2020)
Nowadays, Ad-hoc wireless networks or mesh networks are receiving great research interest due to their great potential in different environments. This paperfocused on the simulation of the performance and energy consumption of Ad-hoc network devices in different configurations. NS-3 was used for this purpose due because it is a modifiable modern program with open code. At first, it was believed that this simulator isideal for this purpose, but in a real sense, there are some missing resources on the energy module. Even though NS-3 was developed as an open-source program by a group of volunteers, this project will be helpful to those that intend to start with NS3 programming or to study energy consumption in simulations. Having understood the program and its function, it will be evaluated for energy consumption patterns in Ad-hoc networks and the likely problems itcould encounter.The features of the ad-hoc throughput (packets) are captured in the analytical model as the energy demand for different ad hoc scenarios is a function of the number of nodes. The results show great improvement in wireless network performance.